Efficacy and safety of BORTEZOMIB treatment for refractory acute antibody‐mediated rejection—a pilot study. (21st December 2018) - Slatinska, Janka; Slavcev, Antonij; Honsova, Eva; Hruba, Petra; Kratochvilova, Iva; Rohal, Tomas; Viklicky, Ondrej
Abstract : A novel therapeutic approach to refractory acute antibody‐mediated rejection (AMR) in kidney transplant recipients was applied in 23 patients based on administration of Bortezomib, intravenous corticosteroids, plasmapheresis and Rituximab. Application of Bortezomib regimen led to diminishing of donor‐specific antibodies (DSA) to HLA‐B ( P = 0.004) and HLA‐DR ( P = 0.0005), but not to HLA‐A ( P = 0.106) and HLA‐DQ antigens ( P = 0.18). Patients with good clinical response to treatment had significantly better allograft survival than recipients with continuing deterioration of graft function ( P = 0.019). Graft survival after therapy of refractory AMR was significantly worse than survival after first transplantation and was comparable with outcomes after retransplantation. In conclusion, therapy with Bortezomib was well tolerated and effective in decreasing the levels of HLA‐B and ‐DR antibodies, however, was not successful in depleting HLA‐A and ‐DQ DSA.